A randomized controlled trial of high parenteral protein feeding in septic children: the role of tumor necrosis factor-alpha-308 polymorphism (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Septic children cause high protein degradation and inadequate nutritional intake would worsen the outcomes. In addition, there are conflicting results of association between tumor necrosis factor-α (TNFA)-308 polymorphism and poorer outcomes. This study was aimed to investigate the impact of high protein feeding in septic children and to examine the role of the TNFA-308 polymorphism in outcome of sepsis. METHODS In this randomized controlled trial, septic children were randomly assigned to receive either high protein feeding (amino acid of 4 g/kg of body weight [kgBW]/day) or standard nutrient (amino acid of 2 g/kgBW/day) for three days in the pediatric intensive care unit of four hospitals in Indonesia. The patientâs enrollment was done between April 2016 and May 2017. The primary outcome was the pediatric logistic organ dysfunction (PELOD) score. TNFA-308 polymorphism was investigated using restriction fragment length polymorphism method in both groups. PELOD score was analyzed as mean differences and gene polymorphism was analyzed with mortality in a subgroup. RESULTS There were 40 children in each group. PELOD score on day-1 (22.4 versus 20.5, p = 0.429), day-2 (20.5 versus 19.8, p = 0.815), and day-3 (18.8 versus 19.8, p = 0.772) were not lower in high protein feeding compared to standard feeding. TNFA-308 polymorphism had no role in mortality of both groups (high protein, p = 0.426; standard, p = 0.456). CONCLUSIONS From this study, researchers concluded that a high protein intervention did not significantly decrease the PELOD score, length of stay, and duration of ventilator use in both groups.